Introduction of Salsola incanescens as a Native Species with a Medicinal, Economic, and Suitable Value for Plantation in Arid and Semi-Arid Regions of Iran (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Arid and semi-arid regions are among the important and valuable areas of natural resources. And covers a wide area of Iran. It is no exaggeration to say that more than half of the area and population of Iran consists of arid and semi-arid rangelands. Salsola incanescens is a valuable species in arid and semi-arid rangelands. In this article, we introduce the perennial species Salsola incanescens, which has high medicinal properties and economic value for rangeland owners and can be used to improve and regenerate arid and semi-arid regions. For this purpose, first, the habitat and uses of this species Indigenous Knowledge for the treatment of diseases and livelihood were identified using the information of local people. Then, some Salsola incanescens seeds were planted in plastic pots and after transfer to the field, their growth and development stages were monitored. The general results of this article indicate the importance of this very valuable plant species for breeding and regeneration in arid and semi-arid regions and other economic uses such as preparing animal Forage and using the ash of this plant for processing raisins and medicinal and industrial properties Be.